Pernikahan Beda Agama dalam Tafsir Bugis: Studi Penafsiran AGH. Daud Ismail atas Q.S. Al-Baqarah [2]:221 dan Q.S. al-Māʾidah [5]:5 - Syam, Muhammad Asrul (Jurnal Moderasi, 2021)
Islamic legal and intellectual tradition recognizes two categories of inter-religious marriages: non-Muslim men marrying Muslim women and Muslim men marrying non-Muslim women. There is a widespread agreement for the prohibition of the first category, but there are differences of views regarding the second. This article examines the interpretation of AGH. Daud Ismail on QS. al-Baqarah [2]:221 and QS. al-Māʾidah [5]:5, two verses that are the basis of differing views on inter-religious marriage the second category. Using the analysis of Hans-Georg Gadamer's Hermeneutics, this study first introduces biographical sketches, intellectual journeys, and the works of AGH. Daud Ismail. The second step is to parse, translate and explain the interpretation of AGH. Daud Ismail. This study reveals that AGH. Daud Ismail recognizes the validity of inter-religious marriage the second category, with a specification of free women from among Ahl al-Kitāb, namely Jews and Christians. The background for his recognition is that he is influenced by the tafsir tradition that he widely referenced.